Performance of hump slab track in sandstorms using simulation and a wind tunnel experiment - Masoud Fathali; Mohammad Mohsen Kabiri Nasrabad; Fereidoon Moghadasnejad (Journal of Engineering and Applied Science)
Abstract Sandstorms have destructive effects on railway infrastructures due to the movement and erosion of sand. One of the proposed solutions to reduce the impact of windblown sand on desert railways is the hump slab track superstructure. This system entails removing the ballast layer and elevating the rails using concrete foundations called humps, which create sand movement channels beneath the rails. The hump’s geometry must not only meet optimal aerodynamic conditions but also ensure ample clearance for sand passage, maintaining structural stability and efficient railway performance. In this study, the aerodynamic evaluation of various hump geometry is examined considering the elliptical (EL) and semicircular-rectangular (CR) shapes. Simulations are carried out using 3D computational fluid dynamics in ANSYS Fluent software. A gas–solid two-phase model, comprising a distinct phase for sand particles and another for air, is developed to assess the sand movement capacity through the selected hump geometries. A wind tunnel experiment is then performed on a prototype of a hump slab track to validate the software model. The findings highlighted that the CR shape, with a height of 25 cm, resulted in the most favorable outputs.